Public sustainable transportation planning with service level efficiency: Hamburg case study - Majid Sodachi; Pardis Sahraei; Omid Fatahi Valilai (Data Science in Maritime and City Logistics: Data-driven Solutions for Logistics and Sustainability. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 30, 2020)
Purpose: Public transportation in large cities has significant impacts on the environmental, social, and economical perspectives. However, the proper assignment of re-sources in public transportation creates paradoxical challenges since by increasing service level efficiency, the environmental criteria will be violated. This paper has studied the literature and discussed the considerable gap for the fulfillment of the mutual service level satisfaction and environmental emission considerations. Methodology: The paper has applied the well-known assignment problem tech-nique and multi-objective planning to propose a novel framework for public transportation resource assignment fulfilling the aforementioned perspectives mutually. The model is capable of analyzing the tradeoffs for increasing public service satisfactions and meanwhile to control the environmental emissions. Using the multi-objective analytical capabilities, the proposed model improves the overall citizens' satisfaction and also manage the operational costs related to the produced emission by transportation resources. Findings: The real data of Hamburg public transportation has been used to verify the capabilities of the proposed model. The findings first validate the model formulation and also gives insights for effective strategic planning for public resource assignment. The analysis emphasizes on establishing control mechanism for passenger's arrival rate as it affects both waiting times in bus stops and also the transportation vehicle weights which drastically affect the environmental factors. Originality: This paper has studied the related literature and discussed the gap for the mutual fulfillment of passenger's service level satisfaction using public transportation and also controlling environmental emissions of public transportation.
urn:nbn:de:gbv:830-882.0115589; hdl:10419/228915; https://econpapers.repec.org/RePEc:zbw:hiclpr:30
Keywords: 650; Logistics; Industry 4.0; Supply Chain Management; Sustainability; City Logistics; Maritime Logistics; Data Science